2016
DOI: 10.1093/jmcb/mjw043
|View full text |Cite
|
Sign up to set email alerts
|

AMPK activation by peri-sciatic nerve administration of ozone attenuates CCI-induced neuropathic pain in rats

Abstract: Neuropathic pain is a debilitating clinical condition with few efficacious treatments, warranting development of novel therapeutics. Ozone is widely used as an alternative therapy for many different pain conditions, with exact mechanisms still elusive. In this study, we found that a single peri-sciatic nerve injection of ozone decreased mechanical allodynia and thermal hyperalgesia, and normalized the phosphorylation of protein kinase C γ, N-methyl-D-aspartate receptor, and extracellular signal-regulated kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 50 publications
0
17
0
1
Order By: Relevance
“…23,24 Our previous study demonstrated that medical ozone could attenuate neuropathic pain by activating AMPK. 25 We also demonstrated that AMPK activation could inhibit neuroinflammation via upregulate SOCS3 expression to suppress the TLR-4/p38 signaling pathway. 26 The aforementioned studies encouraged us to explore the potential protective effects of ozone therapy on chemotherapeutic enteritis and to investigate the role of AMPK/SOCS3-mediated negative inflammatory feedback in the strategy.…”
Section: Introductionmentioning
confidence: 68%
“…23,24 Our previous study demonstrated that medical ozone could attenuate neuropathic pain by activating AMPK. 25 We also demonstrated that AMPK activation could inhibit neuroinflammation via upregulate SOCS3 expression to suppress the TLR-4/p38 signaling pathway. 26 The aforementioned studies encouraged us to explore the potential protective effects of ozone therapy on chemotherapeutic enteritis and to investigate the role of AMPK/SOCS3-mediated negative inflammatory feedback in the strategy.…”
Section: Introductionmentioning
confidence: 68%
“…LULIN MA 1 , SONG WEN 1 , JIE YUAN 1,2 , DEXIN ZHANG 1 , YAN-LIU LU 3 , YOU ZHANG 4 , YING LI 1 and SONG CAO 1,2 oxidative and anti-pathogenic effects and immune regulation ability, as well as the increase of oxygen supply and reduction of oxidative stress (12,(20)(21)(22)(23)(24)(25)(26)(27). For instance, ozone was proven to relieve pain by causing the following effects: i) Release of endorphins (26); ii) inhibition of the activation of microglia via adenosine monophosphate (AMP)-dependent protein kinase signaling (28); iii) inhibition of the expression of purinergic receptors P2X3 and P2X7 in the spinal dorsal horn (29); iv) promoting phosphodiesterase 2A-cyclic guanosine monophosphate/cyclic AMP/NFκB-p65 signaling (30); v) inhibition of autophagy (31,32); vi) reduction of the expression of pro-inflammatory/pro-apoptotic caspases (33); and vii) increase of oxygen supply in tissues and cells (22).…”
Section: Detection Of Chlorite Chlorate and Perchlorate In Ozonated mentioning
confidence: 99%
“…RNA isolation, reverse transcription and quantitative PCR [20] in vitro analy-5 collected, and total RNA was isolated as well. cDNA was ---Western blotting analysis 6 2 -2 at room temperature [22] Statistical analysis dent's t P<0.05 was considered Emodin decreased polarization of AAMs during acute allergic ment [11] . Therefore, we determined whether emodin attenuates in vivo in a murine asthma model.…”
Section: Murine Asthma Modelsmentioning
confidence: 99%